Особливості формування оборотних активів у різних форматах підприємств роздрібної торгівлі - Власова, Наталія Олексіївна; Михайлова, Олена Валентинівна (Харківський державний університет харчування та торгівлі, 2014)
Наведено результати досліджень щодо динаміки загального розміру та основних складових оборотних активів у сумі та днях обороту, змін їх структури в різних групах сучасних форматів підприємств роздрібної торгівлі продовольчими товарами. Це дозволило виокремити особливості формування оборотних активів, які необхідно враховувати під час прийняття ефективних управлінських рішень.

Effectiveness of the retail trade enterprises’ functioning to a large extent is defined by size and composition of the circulating assets which form a significant part of the common sum of assets. On the one hand, movement mobility, composition complexity, correction and variety of direction of elements usage, and on the other hand, high dependence from environment, branch factors, type and size of enterprises lead to necessity in research of formation peculiarities of the circulation assets. Development of modern formats of the retail trade in Ukraine, change of business trends, also defines the necessity in researching this process. The given material covers the results of tendencies research of quantitative and qualitative changes of the circulating assets in the middle and large enterprises of the food products retail trade of "supermarket" and "hypermarket" type. Discovered discrepancies and peculiarities of the circulating assets formation allow to increase the reasonableness of management decisions of the examined enterprises’ types.
Peculiarities of the circulating assets formation in the different formats of the retail trade enterprises
Keywords: товарні запаси; дебіторська заборгованість; грошові засоби; роздрібний товарооборот; підприємства торгівлі; динаміка; структура; circulating assets; trade stocks; accounts receivable; monetary funds; retail turnover; dynamics; structure